PROFIL KEPRIBADIAN INTROVERT BERPRESTASI TINGGI DAN BERPRESTASI RENDAHKELAS VIII DI SMP N 5 TANAH PUTIH T.P. 2013-2014 - Roaita '; Raja Arlizon Raja Arlizoni; Abu Assyari Abu Asyari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrac : Pursuant to result of observer of writer to class student of VIII in SMP N 5 White Land;Ground of T.P 2013-2014 , Seen the existence of problems concerning introvert personality of student  have high achievement to and introvert personality of student  have low achievement to. Target of this research is to know introvert personality picture of student  have high achievement to and introvert personality of student  have low achievement to. This research is done/conducted by using method of diskriptife. Research population is entire/all class of VIII in SMP N 5 White Land;Ground of year 2013-2014 amounting to 88 people. This enquette in using to collect data represent enquette closed. Result of research of this skripsi indicate that : common/ public picture of personality profile from result of data-processing result and research which in making by researcher, hence can be taken by conclusion that : A. In general introvert personality profile picture ofstudent  have high achievement to of class of VIII in SMP N 5 found by White Land;Ground 28 student people ( 56%) from 50 student people 1) impulsion aspect from 50 student people found by 28 student people ( 56%) 2) Feeling aspect from 50 student people found by 30 student people ( 60%) 3) Aspect contemplative faculties from 50 student people found by 34 student people ( 68%) 4) Aspect Responsibility from 50 student people found by 26 student people ( 52%).B. picturely introvert personality profile of student  have low achievement to of class of VIII in SMP N 5 found by White Land;Ground 10 student people ( 25%) from 38 student people 1) Activity aspect found by 22 student people ( 59,9%) from 38 student people 2) Hobby aspect associate with to be found by 22 student people ( 57,9%) from 38 student people 3) Aspect take decision found by 21 student people ( 55,2%) from 38 student people. Keyword: Introvert Student  have High Achievement And have Low Achievement .